The Sun, 16 July 2007 - Tham,Cindy (Sun Media Corp.Sdn.Bhd., 2007)
The Federal, Constitution of Malaysian was first known as the Malayan Independence Constitution- aptly named for a nation that had just gained independence from colonial rule.